Asymmetric aminohydroxylation route to (+)-L-733,060 - Kandula, Subba Rao V.; Kumar, Pradeep (Tetrahedron-Asymmetry, 2005)
An enantioselective synthesis of (+)-L-733,060 starting from cinnamic acid using Sharpless asymmetric aminohydroxylation and Wittig reactions as the key steps is described. (c) 2005 Elsevier Ltd. All rights reserved.

Asymmetric synthesis of (-)-alpha-conhydrine - Kandula, Subba Rao V.; Kumar, Pradeep (Tetrahedron-Asymmetry, 2005)
The enantioselective synthesis of (-)-alpha-conhydrine has been achieved by two different synthetic routes. The key steps include Sharpless asymmetric dihydroxylation, regioselective opening of a cyclic sulfate and Wittig olefination. (c) 2005 Elsevier Ltd. All rights reserved.

Asymmetric aminohydroxylation route to cis-2,6-disubstituted piperidine-3-ol: application to the synthesis of (-)-deoxocassine - Kandula, Subba Rao V.; Kumar, Pradeep (Tetrahedron, 2006)
A highly efficient, flexible, and convergent route to cis-2,3,6-trisubstituted piperidines has been developed employing the Sharpless asymmetric aminohydroxylation and stereoselective reductive amination by catalytic hydrogenation as the key steps. Its usage is illustrated by the short synthesis of the piperidine-3-ol alkaloid, (-)-deoxocassine. (c) 2006 Elsevier Ltd. All rights reserved.

Dimethyl sulfoxide pivaloyl chloride: a new reagent for oxidation of alcohols to carbonyls - Dubey, Abhishek; Kandula, Subba Rao V.; Kumar, Pradeep (Synthetic Communications, 2008)
An efficient procedure for conversion of alcohols to the corresponding carbonyl compounds, an alternative to the classical Swern oxidation, is described. Pivaloyl chloride is employed as a mild and inexpensive electrophile. A possible reaction mechanism is proposed.
Keywords: Alcohols; carbonyls; DMSO; pivaloyl chloride; Swern oxidation